2015
DOI: 10.1093/molbev/msv341
|View full text |Cite
|
Sign up to set email alerts
|

VHICA, a New Method to Discriminate between Vertical and Horizontal Transposon Transfer: Application to theMarinerFamily withinDrosophila

Abstract: Transposable elements (TEs) are genomic repeated sequences that display complex evolutionary patterns. They are usually inherited vertically, but can occasionally be transmitted between sexually independent species, through so-called horizontal transposon transfers (HTTs). Recurrent HTTs are supposed to be essential in life cycle of TEs, which are otherwise destined for eventual decay. HTTs also impact the host genome evolution. However, the extent of HTTs in eukaryotes is largely unknown, due to the lack of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
85
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(87 citation statements)
references
References 57 publications
2
85
0
Order By: Relevance
“…This unprecedented figure is more than four times higher than the total number of HTT events reported so far in metazoans, plants, and fungi combined (10). Such a high number is still not unexpected, given that studies focusing on one or a few TEs often found one or more HTT events between multiple, distantly related taxa (11,(14)(15)(16)22).…”
Section: Significancementioning
confidence: 77%
See 3 more Smart Citations
“…This unprecedented figure is more than four times higher than the total number of HTT events reported so far in metazoans, plants, and fungi combined (10). Such a high number is still not unexpected, given that studies focusing on one or a few TEs often found one or more HTT events between multiple, distantly related taxa (11,(14)(15)(16)22).…”
Section: Significancementioning
confidence: 77%
“…We identified clades of related insect species for which this situation may happen, by relying on the common assumption that inherited TEs evolve neutrally and similarly to synonymous sites of protein coding genes (20). This assumption implies that TEs showing higher interspecific homology than the synonymous sites of orthologous genes should share a more recent ancestor than the host species, and hence be the result of HT (16,21). Conversely,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For species for which genomes are available, HTT was estimated using the vhica R package (Wallau et al ., ). As can be seen in Fig.…”
Section: Resultsmentioning
confidence: 97%